Il nazionalismo russo, 1900-1914: identità, politica, società - Savino, Giovanni (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2022)
Giovanni Savino Russian Nationalism, 1900-1914: identity, politics, society gives a reconstruction of the debate and the issues of National Conservative area in Late Imperial Russia, going through the main positions and topics at the core of State Duma and public opinion debates. Great attention is devoted to the role of Conservative intellectuals in the formation of programs and ideas, as to the Kholm question, which saw the clash with the Polish National Movement, and the relation with the Ukrainian identity.